2009
DOI: 10.1152/ajplung.90530.2008
|View full text |Cite
|
Sign up to set email alerts
|

Targeted inactivation of endothelial lipase attenuates lung allergic inflammation through raising plasma HDL level and inhibiting eosinophil infiltration

Abstract: Endothelial lipase (EL) is a novel phospholipase that determines plasma high-density lipoprotein cholesterol (HDL-C) levels. We have investigated the role of HDL-C in lung allergic inflammation by using EL knockout (EL-KO) mice that are high in HDL-C. EL-KO and wild-type control mice were sensitized and challenged with ovalbumin to evoke eosinophilic inflammation in the lung. EL was expressed in epithelial cells, alveolar type II cells, and endothelial cells in the lung, and its expression was upregulated duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 52 publications
1
19
0
1
Order By: Relevance
“…In 2005, ABCA1, representing the fi rst step in reverse cholesterol transport, was reported to be essential for maintaining normal lipid composition, architecture, and airway physiology of the lung ( 4 ). In 2009, genetic deletion of endothelial lipase was shown to increase HDL nearly 2-fold, which was credited with decreasing AHR and pulmonary infl ammation in ovalbumin (OVA)-sensitized mice ( 5 ). In 2010, we reported that genetic deletion of apolipoprotein (apo)A-I specifi cally increased pulmonary infl ammation and AHR without impairing peripheral vascular function ( 6 ).…”
Section: Airway Resistancementioning
confidence: 99%
“…In 2005, ABCA1, representing the fi rst step in reverse cholesterol transport, was reported to be essential for maintaining normal lipid composition, architecture, and airway physiology of the lung ( 4 ). In 2009, genetic deletion of endothelial lipase was shown to increase HDL nearly 2-fold, which was credited with decreasing AHR and pulmonary infl ammation in ovalbumin (OVA)-sensitized mice ( 5 ). In 2010, we reported that genetic deletion of apolipoprotein (apo)A-I specifi cally increased pulmonary infl ammation and AHR without impairing peripheral vascular function ( 6 ).…”
Section: Airway Resistancementioning
confidence: 99%
“…Studies of Lipg − /Lipg − knock out mice have demonstrated multiple roles for LIPG in vascular lipoprotein metabolism, including serving potential roles in blood vessel inflammation (Kojima et al, 2004), promoting low-density lipoprotein cholesterol (LDL-C) uptake in macrophages (Yasuda et al, 2007), modulating allergic asthma (Otera et al, 2009), HDL-C mediated repression of leukocyte adhesion (Ahmed et al, 2006) and influencing HDL particle size in the circulation (Jin et al, 2003). Clinical studies have also examined LIPG genetic variants in human populations with loss of function LIPG mutations leading to increased HDL-C levels and an associated protection from atherosclerotic cardiovascular disease (deLemos et al, 2002; Edmondson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Npc1l1 is a separate gene expressed in gut epithelium [36], [37], [38], [39], [40], [41] whose protein product regulates cholesterol absorption, thereby influencing whole body cholesterol homeostasis, and is the target of ezetimibe. A growing body of literature implicates cholesterol or modulators of metabolism in the regulation native airway responsiveness and/or allergic airway inflammation [42], [43], [44], [45], [46], [47]. Depletion of cholesterol from membrane caveoli disrupts contractile activation of airway smooth muscle during muscarinic, serotonin, or KCl-stimulation [48], [49], and further inhibits rho kinase activation [48].…”
Section: Discussionmentioning
confidence: 99%